2000
DOI: 10.1016/s0013-4686(00)00496-5
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical behaviour of CuZn under conditions of illumination

Abstract: The influence of UV illumination on the passive behaviour of Cu37Zn in pH 9.2 and 13.0 chloride-containing electrolytes was studied using potentiodynamic polarisation tests, cyclic voltammetry and complex impedance spectroscopy. It was found that UV illumination exerted a slight activating effect on the passive behaviour in the alkaline pH 13.0 solution, with slightly higher passive current densities being recorded under conditions of illumination. A more pronounced UV illumination effect was observed in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Localized corrosion resistance was significantly improved in the lower potential range, where zinc itself is active. Rudd and Breslin reported that UV illumination has an activating effect on the passivation of Cu-37Zn in chloride containing borate buffer [20]. Their results were explained in terms of the nature of complex films involving ZnOAExH 2 O and Cu 2 O/CuO oxides.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Localized corrosion resistance was significantly improved in the lower potential range, where zinc itself is active. Rudd and Breslin reported that UV illumination has an activating effect on the passivation of Cu-37Zn in chloride containing borate buffer [20]. Their results were explained in terms of the nature of complex films involving ZnOAExH 2 O and Cu 2 O/CuO oxides.…”
Section: Introductionmentioning
confidence: 98%
“…Passivation in slightly alkaline solution, with and without addition of chloride, has not received much attention [15][16][17][18][19][20]. The passivation behaviour of brasses under these conditions is interesting since the passivation of the copper and zinc components occurs at a pH value of 9 [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brass is an alloy (Cu-Zn) commonly used for decoration purposes and also in heating exchanging systems, e.g., desalination and power generation plants [1,2]. The corrosion behavior of brass has been extensively studied in a wide range of experimental conditions, with specific interest in the dezincification [3][4][5], passivation, and pitting corrosion [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%